2021
DOI: 10.1177/10996362211033896
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic response of sandwich beams with lattice and pantographic cores

Abstract: Mechanical performance of 3d-printed polyamide sandwich beams with different type of the lattice cores is investigated. Four variants of the beams are considered, which differ in the type of connections between the elements in the lattice structure of the core. We consider the pantographic-type lattices formed by the two families of inclined beams placed with small offset and connected by stiff joints (variant 1), by hinges (variant 2) and made without joints (variant 3). The fourth type of the core has the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…The erosion condition for the finite elements was defined according to the maximum tensile pressure criterion 35,57,58 . This criterion is recommended by the explicit materials library of ANSYS for different polymeric materials and in our previous work we found that this criterion provided good agreement with experimental data 33 . In the simulations, the tangent modulus was defined as E s /12 and the limiting stress was σ = 1.1σ s that allowed us to approximate the typical stress-strain diagram of the considered solid material.…”
Section: Numerical Simulationsmentioning
confidence: 59%
See 1 more Smart Citation
“…The erosion condition for the finite elements was defined according to the maximum tensile pressure criterion 35,57,58 . This criterion is recommended by the explicit materials library of ANSYS for different polymeric materials and in our previous work we found that this criterion provided good agreement with experimental data 33 . In the simulations, the tangent modulus was defined as E s /12 and the limiting stress was σ = 1.1σ s that allowed us to approximate the typical stress-strain diagram of the considered solid material.…”
Section: Numerical Simulationsmentioning
confidence: 59%
“…8c), while the drop of equivalent strain arises in the ideal lattice already at t = 2 ms, when the struts experienced the local failure and buckling. Notably, that this effect can be related to the change of the stress state triaxiality, when the shear deformation become negligible in the sharp interpenetrated contacts between the struts in the ideal structure and the most dangerous triaxial tension become intensive and initiate the through crack propagation over the over-loaded joints of the struts 33 .…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Duke et al 31 studied the nonlinear dynamics and vibrations of a composite cylindrical sandwich material with auxetic alveolar cores on elastic foundations subjected to mechanical stresses. Conventional and auxetic honeycombs were compared in uniaxial and biaxial milling by Li et al 32 The static and dynamic response of 3D printed sandwich beams was studied by Solyaev et al 33 In the present work, the study of the vibrational behavior of bio-sandwich structures with auxetic and non-auxetic cores was carried out using numerical studies of finite element simulations and experimental tests. Three different types of core were produced (re-entrant, rectangular and hexagonal) and for each of these configurations, four elementary cell densities were evaluated depending on the width of the specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Duke et al 31 studied the nonlinear dynamics and vibrations of a composite cylindrical sandwich material with auxetic alveolar cores on elastic foundations subjected to mechanical stresses. Conventional and auxetic honeycombs were compared in uniaxial and biaxial milling by Li et al 32 The static and dynamic response of 3D printed sandwich beams was studied by Solyaev et al 33…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work 33 , we considered similar approach for the plane lattice structures. We discovered that introducing small out-of-plane offsets for the struts resulted in a significant improvement in impact strength, ranging from 3.5 to 5 times in comparison with standard plane lattices, while the static properties of the structures remained mostly unchanged.…”
Section: Introductionmentioning
confidence: 99%